Dampak Work-life Balance dalam Meningkatkan Komitmen Kerja melalui Motivasi Kerja pada Karyawan F&B Gen Z Jawa Tengah dan DIY - Amalia, Shifa Arfina; Ingsih, Kusni; Febriana, Artha; Purwatiningsih, Aris Puji (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to examine how the aligment between professionalism and personal activities affects work commitment, while also testing the extent to which work motivastion plays a role as a link in this corellation among Gen Z employees who work part-time in the food and beverage sector, especially in coffe shop in the DIY region, Central Java. Data collection was conducted through a questionnaire survey with a puposive sampling technique on 158 participants, after which is was analyzed through Partial Least Square Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 3 software. The research findings indicate that all hypotheses are accepted, namely work-life balance has a positive impact on work motivation and work commitment, with motivation as a partial mediator that strenghtens the corellation of harmony between work and personal life with commitment. Work motivation exhibits the strongest influence (path coefficient = 0,659). This study strengthens Boundary Theory through the finding that the harmony between professionalism and personal acts as a resource that drives intrinsic motivation and work commitment, especially in the context of part-time Gen Z employees in the food an beverage sector.